PENILAIAN KINERJA KEUANGAN DAN NON KEUANGAN PADA KANTOR KELUARGA BERENCANA KABUPATEN SITUBONDO - Ramadhani, Dwi Ayu; Titisari, Purnamie; Sayekti, Yosefa (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2017)
Abstract: The performance assessment conducted by the government institutions listed in the Performance Accountability Report of Government Institution (LAKIP) is merely described from the financial perspective. Meanwhile, the main focus of the government organizations is not the financial objective, but its customers, i.e., the community and the central government. This research analyzes financial and non-financial performance assessment of the Family Planning Office in Situbondo Regency by applying the balanced scorecard approach (descriptive analysis method). Data were analyzed following Miles and Huberman’s recommendation: data reduction, data display, and deduction and verification using the triangulation techniques to check data validity. Results show that from the financial perspective, by applying Accrual Financial Information System (SIRKA) the finances can be managed easily, quickly, and precisely. From the customer perspective, the family planning service is in line with customers' expectations based on interview results with several program acceptors in 2015. From the internal business perspective, the performance also has a good achievement. Meanwhile from the growth and learning perspective, the lack of HR personnel inhibits the program implementation that can be overcome by increasing the role of the program’s local assistant (PPKBD) in the villages in Situbondo. Keywords:Performance, Balanced Scorecard, Public Sector Performance.